Beyond Traditional Subtitles: How Emojis and Non-Standard Typography in Subtitles Boost Engagement on TikTok - Duraj, Kinga; Szarkowska, Agnieszka (Journal of Audiovisual Translation, 2025)
The rise of social media platforms, including TikTok, has given way to new and distinct subtitle styles that significantly differ from traditional subtitling norms. However, little is known about what viewers think about these styles or how they affect engagement. This article presents the results of two studies examining the impact of subtitle style on user engagement on TikTok. Study 1, based on an online survey of 171 Polish participants, explored preferences for different subtitle styles on TikTok: traditional subtitles versus those featuring emojis and non-standard typography (i.e., lacking punctuation and capitalisation). The findings revealed a clear preference for subtitles that omit punctuation and capitalisation while including emojis. Study 2 further investigated how these stylistic features influence viewer engagement with subtitled TikTok videos by analysing metrics such as likes, shares, and comments. Videos with non-standard typography attracted higher engagement than those with traditional subtitles. These findings are discussed in the context of digital communication and contemporary subtitling practices, highlighting significant differences between social media subtitles and traditional subtitling on TV and streaming platforms. Lay summary This paper presents the results of two studies aimed to test if subtitle style has an effect on how users engage with TikTok videos. Study 1, which was an online survey with 171 participants, tested user preferences for different TikTok subtitle styles: traditional subtitles with no errors or emojis and subtitles with linguistic errors, such as missing punctuation and capitalisation, and using emojis. The findings showed that viewers preferred subtitles without punctuation marks or capital letters, but with emojis. Study 2 explored how these features influence viewer engagement with subtitled TikTok videos by measuring metrics such as likes, shares, and comments. Videos with incorrect punctuation and capitalisation had higher engagement than those with traditional, linguistically correct subtitles. These findings are discussed in the context of current subtitling practices, highlighting significant differences between social media subtitles and traditional subtitling.